CRIME VICTIMS - Pairote, Rewat (Journal of MCU Nakhondhat, 2024)
When crimes occur in society, experts from various fields will focus on crime cases and criminals more than crime victims. Therefore, the study of victimology will analyze the crime victim's personality, roles of crime victim, relationship between crime victim and criminal, responsibilities of crime victims and criminals, criminal motivations, influences of criminal behavior, and including the crimes without victims and types of criminals. Schafer defines types of crime victims as 7 types and Han Von defines victim defines crime victim types as 13 types that show different types of crime victims leading to different crimes. Therefore, the study of crime victims should consider other factors that contribute to crime such as time, place, season, emotion, age, gender, motivation, etc. Focusing on crime victims will help us to understand the crime problems deeply and avoid blaming criminals. When crimes occur, we need to consider and analyze three parts such as criminal, crime victim, and environment. Therefore, the purposes of the study of the relationship among criminals, crime, and crime victims are to protect crime victims from committing crimes and to increase efficiency in crime prevention and suppression, which will create safety and peace in society.